Antibiotic purification by using metal ion affinity zeolite adsorbent - Saparudin, Wasimin (2010)
Antibiotics are chemical substances that can inhibit the growth of, and even destroy, harmful microorganisms. They are derived from special microorganisms or other living systems, and are produced on an industrial scale using a fermentation process. For a new antibiotic, manufacturers must be able to easily isolate it. For the isolation process, choosing a suitable adsorbent such as zeolite will result in high yield and a better quality of antibiotic product. Impurities from the fermentation process need to be isolate from the antibiotic. The purpose of this research is to use zeolite as an immobilized metal ion affinity stationary phase for antibiotic purification and to study the best parameter in purification process. In this research, zeolite was use as an immobilized metal ion affinity stationary phase for antibiotic purification. The method used in this research to purified the antibiotic was by using adsorption process. The antibiotic used in this research is Rfampicin. Zeolite H-Y and zeolite H-Beta that immobilized with metal ion was used as an adsorbent. Three parameters have been studied to elucidated the best condition for purification process, that is effect of contact time, effect of different pH and effect of different adsorbent. The samples were analyzed Using UV-VIS Spectrometer. The results show that the optimum contact time of adsorption of rifampicin is at 7 minutes. At this time, the zeolite has reached it limit to adsorb impurities. The maximum rifampicin adsorption is at pH 7. Effect of pH is related to pKa of the antibiotic. The third parameter studied shows that the best adsorbent is zeolite that immobilized with metal nikel. From the data and supported theories by various authors, it can be conclude that studied the different condition in adsorption process have a significant effect on antibiotic purification.